Developmental State Policy, Educational Development, and Economic Development: Policy Processes in South Korea, 1961-1979 - Kim, Ki Su (Education Policy Analysis Archives, 2012)
This paper explores two inter-connected issues – the state’s role in educational development and educational contribution to economic development – in the policy processes entailed by the South Korean state’s pursuit of economic development during the Park Chung Hi era, 1961-1979. It disputes the statist view that South Korea’s economic development was the outcome of a strong state’s imposition of developmental policies. It also denies the human capital account that central to the South Korean state’s education policy was the skills formation agendum. In this paper’s process analysis, educational contribution to economic development was made most importantly in the entrance competition-swept schools by virtue of their equipping South Koreans with basic knowledge and intellectual skills and the most important educational asset for economic development was those schools’ explosive growth. The latter took place as an unexpected effect of the state’s developmental policy of containment which aimed to secure scarce funds for strategic developmental projects. This policy intensified entrance competitions, boosted demand for education, and provoked public call for state commitment to educational expansion. The legitimacy-deficient regime responded politically and compromised on the developmental education policy from one level of formal schooling to another. The image of the developmental state thus portrayed is quite contrary to that provided by the statist-human capital perspective.